Lateral condyle fracture of the femur complicated by lateral patellar luxation in two dogs - DiMeo, A.; Bufalari, A.; Bellezza, E.; Pepe, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Two cases of lateral condyle fracture of the femur associated with lateral patellar luxation in the dog are described in this paper. Lateral condyle fractures are rare and difficult to diagnose. If the fracture is not opportunely reduced, the instability of the stifle can cause lateral patellar luxation and severe degenerative joint disease.
Keywords: Dog; femur; fracture; condyle; patella